THE EFFECT OF SOCIAL MEDIA MARKETING AND BRAND AWARNESS ON PURCHASE DECISIONS WITH VIRAL MARKETING AS INTERVENING VARIABLES ON JANJI JIWA COFFEE CONSUMERS AMONG STUDENTS USING SOCIAL MEDIA AREA JABODETA - Muhammad Nurfauzi Awaludin; Sigit Sukmono (AFEBI Management and Business Review, 2020)
The purpose of this study was to analyze the influence of social media marketing and brand awareness on purchasing decisions with viral marketing as an intervening variable in Janji Jiwa coffee consumers among students who use social media in Jabodeta. convenience sampling with samples used as many as 214 respondents to fill out an online questionnaire with certain criteria. This research uses two independent variables, namely social media marketing and brand awareness, the dependent variable is the purchase decision and as an intervening variable (mediation), namely viral marketing. The method used in this study uses path analysis which is the development of multiple linear regression andprocessed using SPSS software. From the research results, it is known that social media marketing has an effect on purchasing decisions both directly and indirectly through viral marketin mediation, and brand awareness influences purchasing decisions both directly and indirectly through viral marketing mediation. Of the two, the direct influence on purchasing decisions is greater than the indirect effect through viral marketing mediation.